Retrospective review of caesarean section wound outcomes in women with class III obesity at a regional hospital in South Africa with a comparison of skin closure techniques; skin staples vs nylon mattress sutures - Khan, Fatima-Zahra (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMed)--Stellenbosch University, 2025.